2013
DOI: 10.1158/0008-5472.can-12-2895
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-204 Expression Enhances Glioma Migration and Stem Cell-like Phenotype

Abstract: Phenotypic similarities have long been recognized between subpopulations of glioma cells and neural stem cells. Many of these similar properties, including the robust abilities to self-renew, migrate and invade, are hallmarks of glioma cells that render them extremely aggressive. However, the molecular mechanisms underlying this character, particularly in glioma stem-like cells that drive this disease, remain poorly understood. Here we report the results of a differential miRNA expression screen that compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 37 publications
11
124
1
1
Order By: Relevance
“…It has an essential role in differentiation of neural stems cells and neural progenitor cells (34 ), and its downregulation promotes growth, invasiveness, and metastasis (35 ) by targeting laminin, gamma 1 (LAMC1), integrin, beta 1 (fibronectin receptor, beta polypeptide, antigen CD29 includes MDF2, MSK12) (ITGB1), cyclin-dependent kinase 6 (CDK6), and SRY (sex determining region Y)-box 9 (SOX9) (36 ). Similarly, miR-204 loss enhanced migration and stem cell phenotype in vivo (37 ). MiR-139 expression was shown to differ between different kidney cancer subtypes (38 ) and was also linked to metastasis and prognosis in ccRCC (39 ).…”
Section: Discussionmentioning
confidence: 93%
“…It has an essential role in differentiation of neural stems cells and neural progenitor cells (34 ), and its downregulation promotes growth, invasiveness, and metastasis (35 ) by targeting laminin, gamma 1 (LAMC1), integrin, beta 1 (fibronectin receptor, beta polypeptide, antigen CD29 includes MDF2, MSK12) (ITGB1), cyclin-dependent kinase 6 (CDK6), and SRY (sex determining region Y)-box 9 (SOX9) (36 ). Similarly, miR-204 loss enhanced migration and stem cell phenotype in vivo (37 ). MiR-139 expression was shown to differ between different kidney cancer subtypes (38 ) and was also linked to metastasis and prognosis in ccRCC (39 ).…”
Section: Discussionmentioning
confidence: 93%
“…First, miR‐204 targets EphB2 in glioma cells (Ying et al ., 2014) and regulates retinal axon guidance through Efnb3 (ephrin ligand) and EphB2 (receptor) during eye development in medaka (Conte et al ., 2014). We speculated that the age‐upregulated miR‐204 targets EphB2 mRNA and reduces EphB2 expression in aged hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…We and other groups have shown that miR-204 is downregulated in multiple human cancers (7,(15)(16)(17)(18)(19)(20)(21)(22)(23). CpG methylation represents an important mechanism responsible for the inactivation of genes, including miRNAs.…”
Section: Discussionmentioning
confidence: 98%
“…TRPM3 and miR-204 share the same transcriptional regulatory motif and are derived from a single transcription unit (28,29). Previous study reported that the promoter CpG islands of TRPM3 were hypermethylated in glioma (21). We next sought to investigate whether the promoter hypermethylation also occurred in colorectal cancer and whether it was responsible for the downregulation of miR-204-5p.…”
Section: Downregulation Of Mir-204-5p Caused By Promoter Hypermethylamentioning
confidence: 99%
See 1 more Smart Citation